Love Cures : Healing and Love Magic in Old French Romance - Doggett, Laine E. (Penn State Romance studies., 2009)
"Examines literary portrayals of women who practice healing and love magic, and argues that these figures were modeled on informally trained practitioners common in the magico-medical paradigm of the high Middle Ages, and were well-respected and successful"--Provided by publisher.